Recent trends in exports of computer software and information technology enabled services from India - Sindhu, Dr. M. (International Journal of Scientific Research and Management (IJSRM), 2020)
Software industry occupies an important place in Indian economy. This sector has a significant role in term of contribution to GDP, employment, export earning etc. The present paper examined the performance of software service exports from India. The software service exports comprises of computer services and information technology enabled serices (ITES). The recent trends in the software export shows that the export earning has increased. The growth rate of export of this sector is 13 per cent during 2008-2019 period. ITES service exports shows a higher growth rate than the computer service exports during 2008-19 period. Though the public limited company was the major contributor of exports, in the last two years the private sector occupies the position. Major destination of software exports are USA and Canada. Majority of the software service exports are through the cross border supply, ie through Mode-1.